S80 Impact Of Peer Educators On Uptake Of Mobile X-ray Tuberculosis Screening At Homeless Hostels: A Cluster Randomised Controlled Trial. (10th November 2014) - Aldridge, R; Yates, S; Hemming, S; Possas, L; Ferenando, G; Garber, E; Hayward, A; McHugh, T; Lipman, M; Story, A
Abstract : Background: The pan London "Find andTreat" tuberculosis (TB) service includes a mobile digital X-ray unit (MXU) screening service which has been shown to be cost effective among hard-to-reach groups (homeless people, substance users and prisoners). This study compared the impact of current practice of hostel staff encouraging MXU screening for TB among homeless people with the addition of peer educators with direct experience of TB and/or homelessness on screening uptake. Design/methods: Between February 2012 and October 2013 London homeless hostels accessing MXU TB screening were randomised to intervention or control arms by minimisation, balancing on hostel size (≤43 beds), and previous screening uptake level (≤50%). Sites with a previous MXU uptake of >80% were excluded. At intervention sites, peers worked with hostel staff to encourage screening (through contacting and speaking with residents). The primary outcome was the proportion of eligible residents screened for TB. Blinding of participants and observers was not possible due to the nature of the intervention. Analysis was performed by intention to treat (ITT). Results: Of 59 hostels considered for eligibility, 46 were randomised (24 allocated to the control and 22 to the intervention arm – Figure 1 ). Across all sites, median uptake was 44% (IQR: 26, 59). Control hostels had a total of 1192 residents [median uptake 45%, (IQR: 33, 55)]. Intervention sites had 1150 residents [median uptake 40%, (IQR: 25, 61)]. Using Poisson regression to account for the clustered study design, size of hostel, and previous screening uptake, there was no evidence for peer educators increasing uptake of screening – adjusted risk ratio 0.98% (95% CIs: 0.80, 1.20). Conclusion: This study found no evidence for peer educators increasing the uptake of MXU TB screening. The wide confidence intervals associated with this result mean that we may be missing a 20% effect, which could be explained by a pragmatic study design where sites were not naïve to the intervention as peers had previously been involved in screening sessions at many hostels. This study was supported by NIHR Programme Grant for Applied Research (RP-PG-0407–10340). Trial registration number: ISRCTN17270334 .